Effect of dynamic visual motion on perception of postural vertical through the modulation of prior knowledge of gravity - Tani, Keisuke; Ishimaru, Sho; Yamamoto, Shinji; Kodaka, Yasushi; Kushiro, Keisuke (Neuroscience letters, 2020)
•We investigated the effects of dynamic visual motion on the perception of body verticality.•Results show the shifts of subjective postural vertical (SPV) after the presence of visual motion with downward acceleration.•The presence of dynamic visual motion can access prior knowledge of gravity, modulating body verticality. To internally estimate gravitational direction and body orientation, the central nervous system considers several sensory inputs from the periphery and prior knowledge of gravity. It is hypothesized that the modulation of visual inputs, supplying indirect information of gravity, affects the prior knowledge established internally by other sensory inputs from vestibular and somatosensory systems, leading to the alteration of perceived body orientation relative to gravity. In order to test the hypothesis, we examined the effect of presenting a visual motion stimulus during a whole-body static tilt on the subsequent evaluation of the perceived postural vertical. Fifteen subjects watched a target moving along the body longitudinal axis directing from head to feet with constant downward acceleration (CA condition) or constant velocity (CV condition), or they did not receive any visual stimulation (NV condition) during the whole-body static tilt. Subsequently, the direction of the subjective postural vertical (SPV) was evaluated. The result showed that the SPV in the CA condition was significantly tilted toward the direction of the preceding tilt compared to that in the NV condition while those in the CV and NV conditions were not significantly different. The present result suggests that dynamic visual motion along body longitudinal axis with downward acceleration can modulate prior knowledge of gravity, and in turn this affects the perception of body verticality.